The sweet potato B-box transcription factor gene IbBBX28 negatively regulates drought tolerance in transgenic Arabidopsis - Dong, Jingjing; Zhao, Cailiang; Zhang, Jie; Ren, Yuchao; He, Liheng; Tang, Ruimin; Wang, Wenbin; Jia, Xiaoyun (Frontiers in Genetics, 2022)
B-box (BBX) which are a class of zinc finger transcription factors, play an important role in regulating of photoperiod, photomorphogenesis, and biotic and abiotic stresses in plants. However, there are few studies on the involvement of BBX transcription factors in response to abiotic stresses in sweet potato. In this paper, we cloned the DNA and promoter sequences of IbBBX28. There was one B-box conserved domain in IbBBX28, and the expression of IbBBX28 was induced under drought stress. Under drought stress, compared to wild type Arabidopsis, the protective enzyme activities (SOD, POD, and CAT) were all decreased in IbBBX28-overexpression Arabidopsis but increased in the mutant line bbx28, while the MDA content was increased in the IbBBX28-overexpression Arabidopsis and decreased in the bbx28. Moreover, the expression levels of the resistance-related genes showed the same trend as the protective enzyme activities. These results showed that IbBBX28 negatively regulates drought tolerance in transgenic Arabidopsis. Additionally, the yeast two-hybrid and BiFC assays verified that IbBBX28 interacted with IbHOX11 and IbZMAT2. The above results provide important clues for further studies on the role of IbBBX28 in regulating the stress response in sweet potato.